Asset Management and Capital Ownership on Firm Value: Through Profitability - Obi Banamtuan; Diana Zuhroh; Sihwahjoeni Sihwahjoeni (Postgraduate Program Merdeka University, 2020)
This study aims to analyze the effect of Asset Management (AM) and Good Corporate Governance (GCG) on stock prices through Return on Investments (ROI). This research is an explanation using quantitative methods. The population of 64 companies is listed on the Indonesia Stock Exchange and is engaged in property and construction. The sampling technique uses purposive sampling with the results of 36 companies. The data used is the 2016-2018 financial statements. The analysis used is path analysis. The results of the study prove that Management asset significantly influences ROI, GCG significantly influences ROI, Management asset significantly influences stock prices, GCG has a significant effect on stock prices, ROI has a significant effect on stock prices, Management asset has a significant effect on stock prices through ROI, GCG has a significant effect on share price through ROI. DOI: https://doi.org/10.26905/afr.v3i1.4296